RESPON PERTUMBUHAN AKSESI KEMANGI PADA BERBAGAI KOMPOSISI PUPUK NITROGEN ALAMI - Rahayu, Arifah; Nahraeni, Wini; Rochman, Nur; Faturrochman, Arif (JURNAL AGRONIDA, 2019)
Basil is not only useful as a vegetable, but also has many medicinal properties. This encourages the development of environmentally friendly basil cultivation, through the use of natural fertilizers. This study aims to determine the response of various basil accessions to the composition of source N fertilizer derived from cow urine, kipahit (Tithonia) compost and Urea. The study was conducted with a factorial completely randomized design. The first factor is the accession of basil, namely Kemang, Ciaruten, Cijujug and Gasol. The second factor is the combination of N fertilizer (10 levels), namely 100% N-Urea, 100% N- cow urine, 100% N-kipahit, 75% N-Urea + 25% N- cow urine, 75% N-Urea + 25 % N-kipahit, 50% N-Urea + 50% N-urine cow, 50% N-Urea + 50% kipahit, 25% N-Urea + 75% N-cow urine, 25% N-Urea + 75% N - kipahit, 0% N-Urea + 0% Ncow urine + 0% N-kipahit. The dosage of N fertilizer used is 150 kg N ha-1. The results showed that the accession of basil which showed good growth and production was 'Ciaruten' and 'Gasol'. The application of Urea fertilizer composition with kipahit compost and Urea with cow urine produces better growth and production compared to the use of Urea fertilizer or organic fertilizer separately. Keywords: basil, cow urine, kipahit compost